P3_5 Fire at Will! - Acton, Jack; Harding, Ben; Kneebone, Ricky; Harvey, Max (Physics Special Topics, 2017)
We consider the force produced by Zarya's "Graviton Surge" in the video game Overwatch. The mass required to produce a gravitational field of the necessary strength is found and the conse- quences of utilising such a mass considered. It is shown that the surge must have a mass of 9.4x10^12 kg, but limitations from special relativity make the existence of such a weapon impossible.